Serum Creatinine Levels Have Been Shown to Accurately Predict in-Hospital Mortality in Individuals who have Been Effectively Treated with PPCI - Iqtidar Ud Din, Muhammad Ahmad Raza Butt, Muhammad Saeed Afridi, Muhammad Suleman Khan, Parveen Akhtar, Mujeebullah Tareen (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study was to assess the predictive value of serum creatinine for in-hospital mortality among patients who had acute coronary syndromes. Study Design: An observational study Place and Duration: This observational study was conducted at Department of Cardiology, Rashid Latif Medical College, Lahore and Nowshera Medical College, Nowshera, KPK in the duration from 1st May, 2022 to 31 October, 2022. Methods: Total 198 patients had acute coronary syndromes who underwent successful primary percutaneous coronary intervention (PCI) were included. Patients were aged between 25-80 years. After receiving written consent, we recorded the subjects’ ages, sexes, BMIs, and diagnoses in detail. Within 12 hours of an AMI diagnosis, serum creatinine levels were taken. Patients were split into two groups based on their serum creatinine levels upon admission. There are two categories, those with high levels of serum creatinine (over 1.3 mg/dL) and those with normal levels (below 1.3 mg/dL). Life expectancy at death was measured at one year. All of the information was analyzed with SPSS 22.0. Results: There were majority 140 (70.7%) males and 58 (29.3%) females in this study. Mean age of the patients was 55.18±11.24 years and had mean BMI was 24.6±14.52 kg/m2. Mean serum urea level was 37.3±0.22 mg/dL. Diabetes found in 40 (20.2%) cases and frequency of hypertension was 82 (41.4%). Anterior myocardial infarction was found in 79 (39.9%) cases followed by Inferior MI in 73 (36.9%) cases and non-ST MI in 46 (23.2%) cases. Mean left ventricular ejection fraction (LVEF) was 45±7.17 %. We found elevated serum creatinine in 37 (18.7%) cases and normal creatinine in 161 (81.3%) cases. Mortality in elevated group was higher found in 10 (27.02%) cases and as compared to normal group 8 (4.96%). Conclusion: The results of this study indicate that patients with AMI who had even slightly raised serum creatinine levels at admission have a significantly higher risk of dying within a year. Keywords: Myocardial Infarction, Comorbidities, Primary percutaneous coronary intervention, Mortality, Serum Creatinine